2022
DOI: 10.3390/ijerph192113797
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Assessment of Agricultural Subsidy Policies on Food Security: Evidence from China’s Poverty-Stricken Villages

Abstract: This paper builds a theoretical model based on a representative peasant household in the neoclassical model, comprehensively considers three types of farmer households in China, and evaluates the effects of the agricultural subsidy policy under equilibrium conditions. Based on the two bottom lines of guaranteeing China’s grain security and ensuring no large-scale return to poverty, this paper uses 2010, 2012, and 2014 tracking survey data from the Mutual Aid Fund for Poverty-Stricken Villages in China to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…It is possible that the risk-reducing effect of agricultural subsidies on the low- and middle-income classes is statistically significant, and that agricultural subsidies would then indirectly affect the volume of grain production by affecting the scale of cultivation [ 33 ]. The willingness to grow grain is likewise an important mechanism affecting the effectiveness of agricultural subsidy policies [ 34 ], and reducing the risk of growing grain may increase the willingness to grow and incentivize rural households to expand the scale of cultivation. However, at the same time, this effect is not thought to be identical across recipients, and there are differences in the effects of agricultural subsidy policies on a rural households’ sown area [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the risk-reducing effect of agricultural subsidies on the low- and middle-income classes is statistically significant, and that agricultural subsidies would then indirectly affect the volume of grain production by affecting the scale of cultivation [ 33 ]. The willingness to grow grain is likewise an important mechanism affecting the effectiveness of agricultural subsidy policies [ 34 ], and reducing the risk of growing grain may increase the willingness to grow and incentivize rural households to expand the scale of cultivation. However, at the same time, this effect is not thought to be identical across recipients, and there are differences in the effects of agricultural subsidy policies on a rural households’ sown area [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…"The 2022 World Food Security and Nutrition Report" showed that though world food production kept pace with population growth, but 828 million people might be affected by hunger and about 2.3 billion people (29.3%) around the world might face moderate or severe food insecurity in 2021. In the continuation to promote the activities of carbon emission reduction in agricultural field, it is necessary to ensure that everyone can buy and afford the basic food they need at any time [4][5][6][7]. In March 2022, the newspaper of "Farmer's Daily" in China, reported "How to Balance Agricultural Carbon Emission Reduction and Growth under the 'Double Carbon' Goal?-Dialogue with Zhao Lixin, Jin Shuqin and Huang Xianjin", and pointed out that agricultural carbon emission (ACE) reduction and agricultural product supply (APS) guarantee are dialectical unity, and the responsibility for agricultural production cannot be shirked in the name of carbon emission reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Subsidies are distributed between landowners and actual operators, and the ratio varies greatly among the different studies within a country or between countries [21][22][23]. Another aspect of research is the effect of direct-agriculturalsubsidy policies on food output [24][25][26][27][28]. The output effect of subsidies mainly depends on the change of farmers' production behavior, including the change of crop-planting area, input of agricultural-production means, and agricultural-labor decision.…”
Section: Introductionmentioning
confidence: 99%
“…The output effect of subsidies mainly depends on the change of farmers' production behavior, including the change of crop-planting area, input of agricultural-production means, and agricultural-labor decision. Some studies show that the direct-subsidy policy has a significant incentive effect on the increase of farmers' planting area and other inputs [17,28,29]. Using tracking survey data, Li et al find that agricultural subsidies can significantly increase the sown area of farmers in povertystricken areas [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation